Students' Perceptions on the Role of Google Translate in Learning English - Suardi Suardi; Tenri Ampareng; Alviani Alviani (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This research aims to determine the perceptions of electronics engineering students regarding the role of Google Translate in learning English. The method used in this research is a qualitative method using a questionnaire instrument to obtain student perceptions. The research results show that 64.7% of students use Google Translate quite often, 76.5% said Google Translate helps them in learning English. However, 82.4% said they had quite difficulty understanding the results from Google Translate. However, Google Translate role in increasing understanding of new vocabulary is quite helpful because 72.2% said it was quite helpful. However, around 39.9% said Google Translate could negatively influence grammar learning. So, it can be concluded that Google Translate has a role in learning English, but it is necessary to analyze the results of Google Translate because it still has several weaknesses, especially in grammar.